Prevalence of overweight and obesity among women of >20 years - Gilla, Sravanthi; Abida, Humera (International Journal Of Community Medicine And Public Health, 2019)
Background: Obesity is a newly emerging, global pandemic problem involving developed as well as developing countries. Even in countries like India, which are typically known for high prevalence of under nutrition, significant proportions of overweight and obese now coexist with the undernourished. Overweight and Obesity are the 5th leading risk of global deaths. Rapidly changing diets and lifestyles are increasing the global obesity epidemic. According to recent estimates, there are more than one billion overweight people worldwide, and some 300 million of these are estimated to be obese. Obesity is one of the important risk factors for non communicable disease like CAD, stroke, cancer, depression etc, going to increase burden of non communicable diseases in terms of morbidity and mortality. Aims and objectives were to determine the prevalence of overweight and obesity among women of >20 years and to identify various factors associated with overweight and obesity. Methods: A community based cross sectional study was conducted and 446 women of 20-60 years age were included in the study. A Predesigned questionnaire was used for the study. Anthropometric measurements such as weight, height, waist circumference were measured using standard techniques. Results: In the present study, prevalence of overweight in the study population was 28.2% and obesity 13.6%. Overweight & Obesity were significantly associated with family history, comorbid conditions etc. Conclusions: Prevalence of overweight & obesity is increasing in developing countries like India due to changing life styles, diet patterns and sedentary life style. This observation emphasizes large scale awareness campaign about overweight and obesity.